Patients With Combined Membranous Nephropathy and Focal Segmental Glomerulosclerosis Have Comparable Clinical and Autoantibody Profiles With Primary Membranous Nephropathy: A Retrospective Observational Study - Gu, Qiu-hua (Medicine (Baltimore), 2016)
Patients with combined membranous nephropathy (MN) and focal segmental glomerulosclerosis (FSGS) have been reported with different clinical significance. Investigations on the possible mechanisms of the combined glomerular lesions are necessary but scarce. Twenty patients with both MN and FSGS lesions were enrolled in the study. Sixty-five patients with primary MN and 56 patients with primary FSGS were used as disease controls. Clinical data on renal biopsy and during follow-up were collected. Circulating anti-phospholipase A2 receptor (PLA2R) antibody, glomerular PLA2R expression, IgG4 deposition, and soluble urokinase receptor (suPAR) levels were detected. We found that patients with combined lesions presented with older age, less proteinuria, higher albumin, and better renal function on biopsy. These were comparable to the patients with primary MN, but differed from the patients with primary FSGS. Patients with combined lesions showed higher stages of MN, no cellular variant on FSGS classification, and more common (100.0%) tubulointerstitial injury than both primary MN and primary FSGS patients. In the patients with combined lesions, 80.0% had circulating anti-PLA2R antibody and 68.4% had IgG4 predominant deposition in glomeruli, which were comparable to primary MN. The patients with combined lesions had significantly lower urinary suPAR concentrations, than the primary FSGS patients (315.6 ± 151.0 vs 752.1 ± 633.9 pg/μmol; P = 0.002), but similar to the primary MN patients (267.9 ± 147.5 pg/μmol). We conclude that patients with combined MN and FSGS may share the same underlying pathogenesis with primary MN. The FSGS lesion might be secondary to primary MN.